Age and sex interactions in mountain ultramarathon running – the Swiss Alpine Marathon - Eichenberger E; Knechtle B; Rüst CA; Rosemann T; Lepers R (Dove Medical Press, 2012)
Evelyn Eichenberger,1 Beat Knechtle,1,2 Christoph Alexander Rüst,1 Thomas Rosemann,1 Romuald Lepers31Institute of General Practice and Health Services Research, University of Zurich, Zurich, Switzerland; 2Gesundheitszentrum St Gallen, St Gallen, Switzerland; 3INSERM U1093, Faculty of Sport Sciences, University of Burgundy, Dijon, FranceBackground: The aims of the study were to examine the (a) participation, (b) difference in running times between the sexes, and (c) age-related decline in the running times of ultramarathoner women and men competing in the Swiss Alpine Marathon from 1998 to 2011.Methods: The ultramarathoners competing in the Swiss Alpine Marathon were analyzed in terms of participation, difference in running times between the sexes, age of the fastest runners, and age-related decline in the fastest running times. The race covers a distance of 78 km, with a total altitude change of approximately 2260 m. A total of 12,194 men and 1781 women finished the race between 1998 and 2011.Results: Women's participation increased from approximately 10% in 1998 to approximately 16% in 2011 (r2 = 0.57; P = 0.001), but participation remained unchanged in men (r2 = 0.17; P > 0.05). Over the years, the top ten women showed no change in running times (r2 = 0.02; P > 0.05), whereas the top ten men's running times increased (r2 = 0.46; P < 0.01). The age for peak running times increased over time both for the top ten women (r2 = 0.58; P < 0.01) and for the top ten men (r2 = 0.40; P = 0.01).Conclusion: Among the top women, participation increased, the age for peak running times increased, and the running times remained unchanged. Among the men, however, the participation remained steady, and both the peak running-time age and the running times increased.Keywords: ultra-endurance, aging, sex difference, running